Synergizing Talent Management and Ethical Work Values to Enhance Engagement and Employee Performance in Higher Education - Suyoto; Bagis, Fatmah; Widhiandono, Hengky (Ilomata International Journal of Management, 2026)
This study investigates whether talent management and values-based ethics are associated with employee performance in higher education, and whether work engagement explains this linkage. Ethical work values in this study are conceptualized as faith-based values rooted in organizational and cultural contexts. We used an explanatory survey design and collected responses from 200 non-academic staff working in public, private, and faith-based universities. The hypothesized relationships were tested using PLS-SEM. The findings indicate that TM is positively related to both engagement and performance. Ethical work values also show a meaningful association with engagement, and engagement functions as a partial mediator in the TM–performance relationship. Furthermore, ethical values amplify the effectiveness of talent management practices in fostering engagement. Integrating talent management with ethical work values provides a value-based human resource management approach that may strengthen employee engagement and performance in higher education institutions. From an applied perspective, the model supports institutional efforts to strengthen quality education (SDG 4) and decent work (SDG 8) by promoting ethical and sustainable HR practices in universities.